Vanishing Children: From High Unemployment to Low Fertility in Developed Countries - Adsera, Alicia (American Economic Review, 2005)
During the last four decades the average total fertility rate in OECD countries witnessed a dramatic fall: from 2.9 in 1960 to 2.0 in 1975 and then to 1.6 in the late 1990s (reaching 1.25 in Southern Europe). With the exception of the United States, all advanced countries now have fertility rates well below the replacement rate of 2.1. In the absence of either sharp changes in fertility behavior or large inflows of immigrants, their populations are set to shrink, particularly in Europe. Still, within this generalized fall, cross-national differences in fertility behavior have remained significant. By 2000, fertility rates ranged from 2.1 in the United States and over 1.8 in France and Norway to less than 1.3 in Greece, Italy, and Spain. Most standard accounts attribute the fall in fertility rates to a shift in personal preferences over the size of the family due to either changes in religious beliefs or growing female participation in the labor market. Yet, even though the ideal number of children for men and women 20–34 years old has declined, it is fairly similar across the European Union at around the replacement level of 2.1 (Eurostat, 2001). Hence, the sources of cross-national variation in fertility behavior must lie somewhere else. As women have joined the labor force, fertility rates have adjusted as a function of the institutional structures that shape the job market and determine its long-run unemployment rate. Exploiting the considerable variation of fertility rates and employment conditions across industrial countries, this paper shows that the current demographic transition is ultimately associated with the constraints of the labor market where fertility decisions are taken.